The sustainability of employee efficiency through moonlighting style - Shaik Baharudin, Siti Sarbanun; Arshad, Mohd Mursyid; Md Rami, Ahmad Aizuddin; Muhamad Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2022)
The term "moonlighting" refers to the practice of holding two or more jobs at different organizations at the same time. Employees moonlight for different reasons, including extra cash, paying off debt, starting a business, and leisure. Low salaries and economic hardships are commonly stated as grounds for moonlighting. Many people believe moonlighting will lead to poor performance, absenteeism, weariness, and career conflicts. Moonlighting has become such a challenge for Human Resource Management that it necessitates numerous thoughtful interventions to ensure employees' effective work performance while also supporting their opportunities for self-growth and development. Work adjustment is revealed by how happy the employees are with the work environment and vice versa. This is called the individual's satisfaction with their job. This also leads employees to moonlight. Work behavior is considered productive or cooperative. When employees are treated like humans, they increase their productivity. If the policy is suitable, an employee will moonlight with authorization, making HR's job easier if they can accomplish their job effectively and contribute to its success. This article summarises moonlighting nowadays. Review articles analyze primary research in new directions, strengthen present theories, or uncover patterns in existing studies. These reviews provide an overview of the literature on employee efficiency through moonlighting.